2014
DOI: 10.1039/c3nr04667b
|View full text |Cite
|
Sign up to set email alerts
|

Integrated random-aligned carbon nanotube layers: deformation mechanism under compression

Abstract: Carbon nanotubes have the potential to construct highly compressible and elastic macroscopic structures such as films, aerogels and sponges. The structure-related deformation mechanism determines the mechanical behavior of those structures and niche applications. Here, we show a novel strategy to integrate aligned and random nanotube layers and reveal their deformation mechanism under uniaxial compression with a large range of strain and cyclic testing. Integrated nanotube layers deform sequentially with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 34 publications
(63 reference statements)
4
26
0
Order By: Relevance
“…Cheng et al [16] reported excellent mechanical properties for CNT film/bismaleimide composites, but its damping ratios decreased with the CNT alignment improvement. The CNT macroscopic assemblies (such as arrays [17,18], fibers [19], films [20,21], and sponges [22,23]) are also found to display structure dependent viscoelastic properties. Korathkar et al [24] fabricated a macroscopic dense-packing CNT film from vertically-aligned nanotube arrays, and the CNT network reinforced sandwich beam manifested a high damping ratio of 0.3.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [16] reported excellent mechanical properties for CNT film/bismaleimide composites, but its damping ratios decreased with the CNT alignment improvement. The CNT macroscopic assemblies (such as arrays [17,18], fibers [19], films [20,21], and sponges [22,23]) are also found to display structure dependent viscoelastic properties. Korathkar et al [24] fabricated a macroscopic dense-packing CNT film from vertically-aligned nanotube arrays, and the CNT network reinforced sandwich beam manifested a high damping ratio of 0.3.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced CNT alignment with associated bundling events during creep was the main cause for property degradation. [ 102,103 ] In those reports, a double-layer composite was compressed and the process was monitored by SEM, which revealed morphology-dominated deformation mechanism (Figure 8 i-k). [ 80 ] A random CNT sponge can be connected tandem with an aligned CNT array, forming a well-defi ned all-CNT composite in series with distinct mechanical behaviors.…”
Section: Structure Reinforcement and Deformation Mechanismmentioning
confidence: 94%
“…Additionally, the initial random entangled CNTs, as shown in Figure 8 h, was evaluated to play a signifi cant role in creep recovery. [ 103 ] Upon unloading, uniform and random networks reappeared in those bundling region due to the CNTs debundling and pores recovery. [ 102,103 ] In those reports, a double-layer composite was compressed and the process was monitored by SEM, which revealed morphology-dominated deformation mechanism (Figure 8 i-k).…”
Section: Structure Reinforcement and Deformation Mechanismmentioning
confidence: 99%
See 2 more Smart Citations